Sex Differences in Internalizing Symptoms and Amygdala Functional Connectivity in Neurotypical Youth. (August 2020) - Padgaonkar, N.T.; Lawrence, K.E.; Hernandez, L.M.; Green, S.A.; Galván, A.; Dapretto, M.
Highlights: Internalizing symptoms in neurotypical youth relate to amygdala connectivity. Greater modulation is observed in females than in males. Connectivity might be a symptom of or a risk factor for disorders. Abstract: Amygdala resting-state functional connectivity (rsFC) is altered in adolescents with internalizing disorders, though the relationship between rsFC and subclinical symptomatology in neurotypical youth remains unclear. Here we examined whether amygdala rsFC varied across a continuum of internalizing symptoms in 110 typically-developing (TD) youths 8 to 17 years old using functional magnetic resonance imaging (fMRI). We assessed overall internalizing symptoms, as well as anxious-depressed, withdrawn-depressed, and somatic complaints. Given known sex differences in the prevalence of internalizing disorders, we compared connectivity between males and females. As compared to males, females with greater internalizing, anxious-depressed, and somatic symptoms displayed greater connectivity with the cingulate gyrus, insula, and somatosensory cortices. In contrast, males with greater anxious-depressed symptoms demonstrated weaker connectivity with the subcallosal prefrontal cortex. Sex differences in rsFC in relation to symptom severity were evident for the whole amygdala and for two of its subnuclei (centromedial and superficial amygdala). Overall, results suggest that, for females, higher internalizing symptoms are associated with greater rsFC between the amygdala and regions implicated in emotional and somatosensory processing, salience detection, and action selection. Future longitudinal investigations are needed to determine whether this hyperconnectivity may confer resilience to, or pose risk for, the development of internalizing disorders.